Testing Anomalies in Multiple and Multilevel Inheritance - Kaur, Shubpreet (My University, 2011)
Software testing is an important phase of software development process that can be easily missed by software developers because of their limited time to complete the project. Thus, Software testing is a widely used and accepted approach for verification and validation of a software system. One of the major challenges in software testing is the generation of test cases that satisfy the given competence criterion. Testing in an object oriented manner significantly increases software reusability, extendibility, interoperability, and reliability. Object oriented testing has to deal with the new problems to deal with the new problems introduced by the new features of Object oriented systems such as inheritance, polymorphism, method overloading, method overriding etc. Object oriented testing technique for testing software units that has great potential for improving the quality of testing and to assure the high reliability of software. In this thesis, we will focus on the features of object oriented systems that create many binding anomalies during static and dynamic binding. This shows that a value of the variable changes with the change in the object if there is given a wrong function call with the object of other class. To detect such anomalies an approach is discussed that will detect static and dynamic anomalies in multiple and multilevel inheritance.
Keywords: Testing Anomalies; Multiple Inheritance; Multilevel Inheritance